Immunohistochemical and molecular expression of laminin-332 gamma-2 chain in canine mammary tumors - Zuccari, D. A. P. C.; Castro, R.; Jardim, B. V. [UNESP]; Mancini, U. M.; Polachini, G. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2011)
Forty-eight cases of canine mammary cancer were investigated to evaluate the immunohistochemical distribution of the gamma 2 chain of laminin-332. Tumor cells were compared to a pool of normal mammary tissues using quantitative RT-PCR. The western blot was performed in eight tumor samples as complementary test to evaluate protein integrity. Immunohistochemistry experiments showed negative, focal, and weak expression of laminin-332 gamma 2 in tumors with the worst prognosis. Quantitative PCR revealed downregulation of the gene in 27 (56.2%) of the animals. Out of the 16 dogs with gamma 2 chain overexpression, seven were still alive. The western blot results showed bands generation of 36, 50, and 98kDa, suggesting degradation of laminin-332 gamma 2 in malignant tumors. The results suggest that, in the future, low expression and/or degradation of laminin-332 gamma 2 chain in canine mammary tumors may be used as an indicator of malignant potential. However, further studies are necessary to corroborate these results.
Expressão imunoistoquímica e molecular da laminina-332 cadeia gama-2 em tumores mamários de cadelas
Keywords: dog; adhesion molecule; cancer; western blot; RT-PCR